Vicious circle: Suicides in Lithuania after the independence - Gailienė, Danutė (Psichologija, 2005)
During the last 80 years suicide mortality in Lithuania has shown great variation. Nowadays Lithuania has the highest registered suicide rate in the world besides the other Baltic countries and Russia. After the sharp decrease in the mid-80’s, since 1991 the suicide rates start to rise again. In 2002 1551 suicide occurred in Lithuania (44.7 per 100.000 persons). The ratio of male to female rates was 4.5–6.1 in 1990–2002, in the young and middle age it reached 8–10. The suicides are more widespread in rural areas. Among rural men they occur twice as often as among the urban and among women – 1.4 times. By age the highest suicide risk is for middle-aged men. Among the males aged 45–54 years suicide rate reaches 154.6. The most common method of suicide remains hanging, both for males and females.The dramatic increase in suicide rates of the early 1990s corresponds to the collapse of the Soviet Union and the regaining of the independence of Lithuania and other Baltic states. Heavy transition from the system based on communist ideology to the open society and market economy was ensuing. However analysis of the trends of suicide mortality in Eastern Europe and in the „newly independent states“ of the former Soviet Union showed that rapid transformations of society do not per se necessarily produce more suicides. Neither the absolute economic changes, nor the level of prosperity in itself correlates significantly with the changes in suicide rates. Intermediate role of culture should be also taken into consideration.The undercurrent reasons of the incredible suicide spread in Lithuania lie in the long lasting effects of the 50 years under the communist regime on the ability of individuals and groups to manage psychosocial stress and changes. „Soviet“ mortality pattern, which is characterized by very high level of premature mortality and growth of urban-rural mortality differences, has not changed during transition period. This leads to vicious circle when the spread of suicides and helpless, indifferent attitude towards suicide prevention, causes the suicide approving attitudes, which increases the risk of suicidal behaviour. The approving attitude towards suicide among Lithuanian schoolchildren increased almost twice over the last decade. The media also „contributes“ to this process, but attempts to change the presentation of suicide in the mass media in 1996–2000 were rather unsuccessful.The national plan of suicide prevention is required to break off the vicious circle.
Keywords: suicide; Lithuania